Performance characteristics of five triage tools for major incidents involving traumatic injuries to children. Issue 5 (May 2016) - Price, C.L.; Brace-McDonnell, S.J.; Stallard, N.; Bleetman, A.; Maconochie, I.; Perkins, G.D.
Abstract: Context Triage tools are an essential component of the emergency response to a major incident. Although fortunately rare, mass casualty incidents involving children are possible which mandate reliable triage tools to determine the priority of treatment. Objective: To determine the performance characteristics of five major incident triage tools amongst paediatric casualties who have sustained traumatic injuries. Design, setting, participants: Retrospective observational cohort study using data from 31, 292 patients aged less than 16 years who sustained a traumatic injury. Data were obtained from the UK Trauma Audit and Research Network (TARN) database. Interventions Statistical evaluation of five triage tools (JumpSTART, START, CareFlight, Paediatric Triage Tape/Sieve and Triage Sort) to predict death or severe traumatic injury (injury severity score >15). Main outcome measures Performance characteristics of triage tools (sensitivity, specificity and level of agreement between triage tools) to identify patients at high risk of death or severe injury. Results: Of the 31, 292 cases, 1029 died (3.3%), 6842 (21.9%) had major trauma (defined by an injury severity score >15) and 14, 711 (47%) were aged 8 years or younger. There was variation in the performance accuracy of the tools to predict major trauma or death (sensitivities ranging between 36.4 and 96.2%; specificities 66.0–89.8%). Performance characteristics varied with the age of the child. CareFlight had the best overall performance at predicting death, with the following sensitivity and specificity (95% CI) respectively: 95.3% (93.8–96.8) and 80.4% (80.0–80.9). JumpSTART was superior for the triaging of children under 8 years; sensitivity and specificity (95% CI) respectively: 86.3% (83.1–89.5) and 84.8% (84.2–85.5). The triage tools were generally better at identifying patients who would die than those with non-fatal severe injury. Conclusion: This statistical evaluation has demonstrated variability in the accuracy of triage tools at predicting outcomes for children who sustain traumatic injuries. No single tool performed consistently well across all evaluated scenarios.